Failed Stakeholder Exchanges and Corporate Reputation: The Case of Earnings Misses - Love, E. Geoffrey; Kraatz, Matthew S. (Academy of Management Journal, 2017)
Corporations engage in ongoing exchange relationships with many different stakeholder groups, and they frequently fail to meet these constituencies’ concrete and firm-specific expectations (regarding profits, products, etc.). While these events bear an intuitive connection to corporate reputation, several scholars have raised questions about the role of discrete exchanges in overall evaluations of firms. Additionally, scholars have neither systematically examined such effects nor elaborated a formal theory thereof. The present paper fills this gap by developing and testing a middle range theory of this important yet poorly understood relationship. This theory identifies the psychological mechanism (trait attribution) which underlies this relationship and explains how discrete, stakeholder-specific exchange failures can damage reputations of larger corporate entities. It also explains how social and historical information associated with failed exchanges can affect this process. We elaborate and test this theory through a study of the effects of quarterly earnings misses on firms’ standing in the Fortune “Most Admired Company” survey. Consistent with our theory, earnings misses did damage firm standing. However, misses did not invariably produce reputational damage and, as predicted, their effects were contingent on associated social (e.g., peer firm reliability, institutional context) and historical (e.g., the firm’s track record and statements) information.